Sistem Akuntansi Peminjaman Dana Bergulir pada BUMDesma “Bumi Artha Mandiri LKD” - Anita Marya (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
The Village-Owned Enterprise (BUMDesma) plays an important role in empowering the local community's economy. BUMDesma "Bumi Artha Mandiri LKD" in Kemujan Village runs a revolving loan program to meet the capital needs of the community, particularly for micro-business actors. This study aims to describe the structure, procedures, and performance of the accounting system applied to the program, as well as to identify obstacles and efforts for improvement. The research method used is qualitative descriptive with data collection through direct observation, interviews with BUMDesma managers and borrower members, and financial document analysis. The results show that the running accounting system includes modules for member registration, lending, payments, and financial reports with recording procedures in accordance with basic accounting principles. The advantages of this system include high transparency and adequate risk control, but it still faces challenges such as limited technology, management capacity, and availability of accurate data. Planned improvements include the adoption of information technology, continuous training, and enhanced cooperation with the community. The study concludes that the existing accounting system has made a positive contribution, but it needs to be strengthened to support the sustainability of the revolving loan program and the economic empowerment of the village.